Is the Tourist Landscape Unique? An Interactive Experience Design Methodology for Tourist Landscape - Yan He, Mingrun Wang (International Journal of Advanced Science and Technology, 2020)
Nowadays, tourists pursue a personalized experience as ordinary or homogeneous tourist landscapes cannot create unique experiences for them. The tourist landscape needs to have personalized characteristics to attract more tourists. However, the lack of an effective experience design method for tourist landscape design has caused most current tourist landscape designs to be insufficiently unique. If the tourist landscape homogenization problem is not solved, its commercial value will be lost. Therefore, tourist landscapes with personalized characteristic designs are needed to experience design methodology to create a unique experience for tourists. A theoretical attract more new tourists to visit the landscapes. This study aimed to spot the landscape interactive framework to understand the tourist landscape interactive experience design methodology was obtained through a literature review. Nine categories of landscape interactive experience design skills were identified through case studies. An effective method of the landscape interactive experience design was obtained through a case application, namely FDV methodology. The results of this study can guide landscape designers to design a unique landscape, thereby promoting its development. Keywords: interactive experience design, landscape design, FDV method.